Contamination of Escherichia coli O157:H7 in dairy cow farms - Faidah Rachmawati; Tati Ariyanti (Indonesian Center for Animal Research and Development (ICARD), 2017)
E. coli serotype O157:H7 is a foodborne pathogen that endangers human health. Cattle are the main reservoir of this bacterium. E. coli O157:H7 that come out of the livestock can contaminate the surrounding environment, dairy products, meat, vegetable or fruit crops, so it can act as a source of infection and disease in humans. This research was conducted to identify the contamination of E. coli O157:H7 on dairy cow farms so the current situation is known. Sampling area for this research was dairy cow farm in Depok, Cianjur, Sukabumi, and Bandung. Types of samples taken are cow anal swab or fresh feces and livestock drinking water. Isolation of E. coli bacteria was done on mTSB media, agar MacConkey, and Eosin Methylene Agar. Identification of bacteria as E. coli O157:H7 was done by biochemical test and for serotype determination was used agglutination test using monospesifik antiserum for O157 and H7. The results of research showed that of the total 178 samples had 126 (70.8%) samples containing E. coli bacteria. Of the 126 samples containing E. coli bacteria, 94 (74.6%) were determined as E. coli serotype O157:H7. The presence of E. coli O157:H7 contaminants on dairy cow farms, their potential impacts on human health, prevention and control of the disease is discussed in this paper.